Physicochemical characterization of georeferenced propolis from 14 locations of Uruguay - Pablo Cracco; María Cristina Cabrera; Giovanni Gallieta (Agrociencia Uruguay, 2023)
Honey bee propolis is studied around the world. Its plant origin, associated with different soils and climates, determines different physicochemical properties. These different properties determine diverse medicinal potentials. Uruguay has few scientific papers that characterize the propolis it produces. This study analyzes propolis from 14 locations of Uruguay, obtained over a year. The vegetation environment of these localities was characterized in a radius of 2 km by satellite images. Color (CIELAB) was measured in ethanolic solution, as well as pH and conductivity in aqueous solution, ashes, total polyphenols (Folin-Ciocalteau) and total flavonoids. The similarities of the localities in terms of their vegetation do not correspond to the similarities between propolis; another method of plant characterization must be used. Differences were found between locations, but not between stations within the same location. The parameters L* and a* are correlated with the polyphenolic content of propolis (R2=0.61 and R2=0.81, respectively). Conductivity is correlated (R2=0.66) with ash content, but it would be necessary to determine what minerals are present to use this tool. The polyphenolic and flavonoid content allows regionalizing the country in southwest and northeast. Southwest with high contents (177 to 262 gGAE/kg and 66 to 131 gQE/kg) and northeast zones with lower contents (27 to 88 gGAE/kg and 10 to 27 gQE/kg). It is necessary to continue studying propolis from Uruguay, its mineral and polyphenol content and its profile in other locations for a longer time.